Draft Fifth Five Year Plan 1974-1979 Volume-I Government of Nagaland - Planning Commission (Planning Commission, 1973)
The State of Nagaland came into existence on 1st December, 1963. the State was constituted of the two districts of Kohima and Mokokchung and by the inclusion of Tuonsang District which was formerly a part of NEFA. the State which covers an area of 16,488 Sq. Kms., lies between 25.6' and 27.4' latitudes and between 93.20' and 95.15' longitudes. the new State is bound by the State of Assam on the northern and western sides, by Burma and NEFA in the eastern, and Manipur on the southern side.
Government of Nagaland, Planning and Co-Ordination Department